THE TRANSLATION OF SLANG AND SWEAR WORDS IN DEADPOOL MOVIE: THE ANALYSIS OF EQUIVALENCE IN THE SOURCE AND TARGET LANGUAGE - Karinda, Ajeng Mediastri (2017)
This qualitative descriptive study aims to analyze the equivalence technique in English-Bahasa Indonesia translation of slang and swear words in Deadpool movie. The concept of formal and dynamic equivalences which is proposed by Nida (1964) is applied in this study as the theoretical framework. Slang and swear words were identified prior to equivalence analysis. For identification, this study applied two concepts: Yule's (1996) word formation processes and Finegan's (2004) lexical semantics. The study found 320 slang and swear words. Synonymy is the most frequent slang and swear words type which appears 145 times (45.31%). In terms of equivalence techniques, this study found that both formal and dynamic techniques are applied by the subtitler. However, dynamic technique is applied more frequently, 200 times (62.50%), than formal technique, 54 times (16.87%). Therefore, in this study, a synonymy-dynamic pattern is the most dominant. Furthermore, a high frequency of untranslated swear words, 66 times (20.62%) is another important phenomenon. Thus, the results indicate that even though the subtitle tends to convey the message of the source language by finding the most natural and the closest equivalences of the original slang and swear words, there is also an ethical or politeness consideration to omit a number of 'rude' and 'abusive' swear words in the target language.----------Penelitian deskriptif kualitatif ini bertujuan untuk menganalisis teknik equivalence di dalam terjemahan bahasa Inggris-bahasa Indonesia pada kata-kata Slang dan Swear di film Deadpool. Konsep formal and dynamic equivalences yang diperkenalkan oleh Nida (1964) diterapkan dalam penelitian ini sebagai kerangka teori. Kata-kata Slang dan Swear diidentifikasi terlebih dahulu sebelum dianalisis equivalence-nya. Untuk identifikasi, penelitian ini menerapkan dua konsep: Konsep Yule (1996) mengenai word formation processes dan konsep Finegan (2004) mengenai lexical semantics. Penelitian ini menemukan ada 320 kata Slang dan Swear. Synonymy adalah tipe kata Slang dan Swear yang paling sering muncul, sebanyak 145 kali (45.31%). Dalam hal teknik-teknik equivalence, penelitian ini menemukan bahwa baik teknik formal maupun dynamic sama-sama diterapkan oleh penerjemah film tersebut. Namun, teknik dynamic lebih sering diterapkan, 200 kali (62.50%), daripada teknik formal, 54 kali (16.87%). Karena itu, di dalam penelitian ini, pola synonymy-dynamic adalah yang paling dominan. Lebih lanjut, frekuensi yang tinggi dari kata-kata swear yang tidak diterjemahkan, 66 kali (20.62%) adalah fenomena penting lainnya. Sehingga, hasil penelitian mengindikasikan bahwa meskipun penerjemah film tersebut cenderung menyampaikan pesan dari bahasa sumber dengan cara mencari equivalence yang paling alamiah dan terdekat dari kata-kata slang dan swear yang asli, terdapat pula konsiderasi etis atau kesopanan untuk menghilangkan sejumlah kata-kata swear yang dinilai 'kasar' dan 'menghina' dalam bahasa target.